2004
DOI: 10.1002/pits.10149
|View full text |Cite
|
Sign up to set email alerts
|

American and Chinese children's understanding of basic relational concepts in directions

Abstract: Two hundred first-and second-grade Chinese children's knowledge of basic relational concepts in following directions was assessed on the Applications Booklet of the Boehm Test of Basic Concepts-Revised (BTBC-R, 1986). Chinese children's performance was then compared with that of the standardization sample of the BTBC-R. Results indicated that both the American and Chinese children made significant improvements between the end of first and second grades, yet both American and Chinese children experienced diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Basic concept skills enable the child to understand and describe relationships among objects, locations of objects and persons, characteristics of objects (dimensions, positions, movements, quantity and presence) and sequences of events (Boehm, 2001). Similarly, knowledge of these concepts is a prerequisite for understanding and following teachers' instructions in all subjects (Zhou & Boehm, 2004). Earlier studies have shown the knowledge of these concepts to predict the child's achievement at the beginning of school (Kavale, 1982;Moers & Harris, 1978;Steinbauer & Heller, 1978).…”
Section: Conceptual Knowledge and School Achievementmentioning
confidence: 99%
“…Basic concept skills enable the child to understand and describe relationships among objects, locations of objects and persons, characteristics of objects (dimensions, positions, movements, quantity and presence) and sequences of events (Boehm, 2001). Similarly, knowledge of these concepts is a prerequisite for understanding and following teachers' instructions in all subjects (Zhou & Boehm, 2004). Earlier studies have shown the knowledge of these concepts to predict the child's achievement at the beginning of school (Kavale, 1982;Moers & Harris, 1978;Steinbauer & Heller, 1978).…”
Section: Conceptual Knowledge and School Achievementmentioning
confidence: 99%
“…Yapılan araştırmalar, çocukların "temel kavram bilgi düzeylerinin" okuma, anlama ve matematik derslerindeki başarıları için ön koşul olduğunu göstermektedir (Bailey ve Wolery, 1992;Boehm, 1971Boehm, , 2000Boehm, , 2001Bracken ve Panter, 2011;Ergül, 2007;Uyanık-Balat, 2009;Zhou ve Boehm, 2004). Ayrıca bu kavramları bilmek, öğretmenin sınıfta verdiği yönergeler ile ders ve alıştırma kitaplarında yer alan yönergeleri takip edebilmek ve uymak için de gereklidir.…”
Section: Brown'un Dilbilgisel Gelişim Evreleriunclassified
“…Okul çağı döneminde de bilişsel gelişim ve akademik başarı ile temel kavramlar arasındaki doğru korelasyon devam ettiği için çocukların temel kavramları edinip edinmediklerini belirlemek önemlidir (Boehm, 1971(Boehm, , 2000(Boehm, , 2001Zhou ve Boehm, 2004). Temel ilişkisel kavramlar önemli düşünce araçlarıdır ve bütün kültürler tarafından karşılaştırma yapmak, sınıflama yapmak ve karışık problemleri çözmek için farklı soyutlama seviyelerinde kullanılır.…”
Section: Brown'un Dilbilgisel Gelişim Evreleriunclassified
See 2 more Smart Citations